2019
DOI: 10.9744/ijbs.2.1.1-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Auditor’s Education Level, Accounting Education, Public Accountant Firm Size on Accounting Profession: Implication to Good Corporate Governance in Indonesia

Abstract: The purpose of this study is to test empirically the influence of auditor education level, accounting education, the amount of public accounting firm to the accounting profession and its implications for the application of the principles of good corporate governance in Indonesia. The research method is descriptive verification by using quantitative approach. Data were collected through indirect communication techniques using questionnaires, limited interviews, and documentation studies in an effort to add expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the 2000s era, the requirements for IT competencies were shifted from a technological view to a more business view (Damasiotis et al, 2015;Soetanto et al, 2020). Many research strengthen the need for accountants to broaden their IT competence on audit automation skills (Brennan et al, 2017;Ernst & Young, 2016;Kokina & Davenport, 2017;Tandiontong et al, 2019), understanding IT governance and IT strategy (Damasiotis et al, 2015), a n d b i g d a t a a n a l yt i c s s ki l l s (Sledgianowski et al, 2017;Richardson & Shan, 2019;Dzuranin et al, 2018;Andiola et al, 2020;Jiputra et al, 2020).…”
Section: It Competence and Accountingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 2000s era, the requirements for IT competencies were shifted from a technological view to a more business view (Damasiotis et al, 2015;Soetanto et al, 2020). Many research strengthen the need for accountants to broaden their IT competence on audit automation skills (Brennan et al, 2017;Ernst & Young, 2016;Kokina & Davenport, 2017;Tandiontong et al, 2019), understanding IT governance and IT strategy (Damasiotis et al, 2015), a n d b i g d a t a a n a l yt i c s s ki l l s (Sledgianowski et al, 2017;Richardson & Shan, 2019;Dzuranin et al, 2018;Andiola et al, 2020;Jiputra et al, 2020).…”
Section: It Competence and Accountingmentioning
confidence: 99%
“…In the last five years, there is more research related to sustainability issues from research on corporate social responsibility (Khan et al, 2020;She & Michelon, 2019), sustainability, and integrated reporting (Bebbington et al, 2020;de Villiers & Sharma, 2020;Journeault et al, 2021), and sustainability issue related to the covid pandemic situation (Adams & Abhayawansa, 2021;Cho et al, 2021). There is also an increasing trend in sustainability reporting worldwide, where accountants play an important role both as preparers or as auditors of the report (Tandiontong et al, 2019). The KPMG survey of sustainability reporting has found that 80 percent of the companies worldwide now report on sustain-ability, and the figure rise over 90 percent among the largest companies in the world (KPMG, 2020).…”
Section: Accounting and Sustainability Issuementioning
confidence: 99%
See 1 more Smart Citation